(untitled) (Baltic Journal of Sport and Health Sciences, 2023)
Background: Studies have shown that exercise modulates brain-derived neurotrophic factor (BDNF) levels, and resistance training, in particular, has received increasing attention for its potential to enhance BDNF production. Most studies investigating exercise-induced BDNF changes have focused on free or mature BDNF, while the measurement of total BDNF, encompassing both proBDNF and mature BDNF, may provide a more comprehensive understanding of BDNF regulation. This pilot study aimed to explore the preliminary effects of resistance training on total BDNF levels in elderly individuals participating in a resistance training program. Methods: A small sample of participants (n=6) was recruited and engaged in a structured resistance training program for 12 weeks, with 6 participants in a control group. Total BDNF levels were measured at baseline and post-intervention using reliable laboratory assessments. Additionally, an isokinetic dynamometer was used to determine muscle strength to explore the effect of the resistance training program on muscle performance. Results: The findings revealed a significant increase in total BDNF levels following the 12 week resistance training intervention (p<0.05). However, improvements in physical performance measures, knee extension peak torque and isometric maximal voluntary contraction, were not observed. Conclusion: In conclusion, this pilot study provides preliminary evidence of the positive effects of a 12 week resistance training intervention on total BDNF levels. The measurement of total BDNF levels serves as an important marker in assessing the response to resistance training. Further research with larger sample sizes and longer intervention periods is warranted to further explore the relationship between resistance training and total BDNF levels and to confirm these preliminary findings. Understanding the impact of resistance training on total BDNF levels can have implications for optimizing training programs and potentially improving exercise-related outcomes. Keywords: muscle strength, exercise, brain-derived neurotrophic factor, neuroplasticity, healthy ageing.